Work Productivity and Digital Fatigue as Determinants of Production Employee Performance in the Pharmaceutical Industry - Lucky Agusman Wihana; Muji Rahayu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid advancement of digital technology has intensified the use of digital devices in daily work processes, including production activities within the pharmaceutical industry. This condition often leads to digital fatigue, which subsequently reduces employees’ work effectiveness. At the same time, work productivity remains a crucial factor in meeting operational standards and ensuring the quality of a company’s output. This study aims to analyze the influence of work productivity and digital fatigue on the performance of production employees at PT Otto Pharmaceutical. This research employed a quantitative approach with an explanatory design. Data were collected using questionnaires distributed to employees through a probability random sampling technique. A total of 135 respondents were analyzed using IBM SPSS Statistics through validity testing, reliability testing, and linear regression analysis. The findings indicate that work productivity has a positive and significant effect on employee performance. Digital fatigue also shows a significant influence, contributing to the decline in performance. Simultaneously, both variables demonstrate a significant contribution to the performance of production employees. These findings suggest that higher levels of employee productivity lead to improved performance, whereas increasing digital fatigue tends to decrease work outcomes. The study provides practical implications for organizational management, particularly in regulating digital workloads, optimizing technology-based work systems, and creating a work environment that minimizes digital fatigue. This research also strengthens empirical evidence regarding the role of productivity and digital fatigue in shaping employee performance within the pharmaceutical industry in the era of digital transformation.